INFORMATION SUPPORT FOR ACTUARIAL ASSESSMENT OF THE FINANCIAL STATUS OF THE PENSION SYSTEM IN RUSSIA - A. K. Solovyev; S. A. Dontsova (Финансы: теория и практика, 2017)
The pension reform 2015 dramatically increased not only the public, but also academic interest to the problems of the national pension system. The discussions revealed serious discrepancies (often diametrically opposed) in the quantitative estimates of both the pension system and the economic and social results of the pension reform, especially in long run. The paper analyzes the composition and structure of statistical data used for actuarial assessments of fi nancial status of the Russian pension system; statistical information resources’ provision needed to assess economic and social impact of the activities conducted within the pension reform; causes and effects of insuffi cient statistical information for forecast evaluation of the pension system balance in the long term.